Outcomes of Fasciotomy in Acute Compartment Syndrome of the Lower Limb - Muhammad Attique Sadiq, Maham Sheraz, Attiq ur Rehman, Muhammad Idrees Achakzai, Hamna Rizwan, Muhammad Nasir Iqbal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Acute compartment syndrome (ACS) of the lower limb constitutes a surgical emergencyrequiring prompt decompressive fasciotomy to avoid irreversible tissue damage, amputation and death. This prospective cohort study aimed